Data-Informed Professional Development for Strengthening Teacher Assessment Literacy in the Digital Era - Hazhar Talaat Abubaker Blbas; Asma Elmar Mansurzada; Tofig Hasanov (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This study examines how data-informed professional development can strengthen teacher assessment literacy amid the growing demands of the digital era. Using a qualitative design, the research combines library investigation and content analysis of scholarly literature published over the past decade related to digital assessment, teacher data literacy, and technology-supported instructional decision-making. Findings reveal that digital transformation in education requires teachers to master data interpretation skills, utilize technology-enhanced assessment tools, and develop ethical awareness regarding privacy and algorithmic bias. However, many teachers continue to face competency gaps, inadequate professional development, and challenges in integrating digital assessment practices effectively. The study highlights that meaningful professional development must be continuous, collaborative, evidence-based, and incorporate data literacy, AI literacy, and reflective pedagogical practice. Such an approach equips teachers to interpret complex data, design valid digital assessments, and make ethically responsible, evidence-driven instructional decisions. This research provides conceptual clarity and a foundation for designing comprehensive professional development frameworks aimed at enhancing teacher assessment literacy within rapidly evolving digital learning environments.